Virtual Learning Environments and Their Influence on Educational Inclusion - Bernate, Jayson; Fonseca, Ingrid (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
The objective of this article is to conduct a systematic review from which a conceptual theoretical body was derived, in order to answer the research question: How do virtual learning environments influence educational inclusion? Thus, with a PRISMA method of inquiry and classification of articles, 8 documents were categorized that allowed us to conclude with the use of Information and Communications Technologies (TIC), faster progress has been observed in the acquisition of knowledge and inclusion in the various processes necessary for individual training.